2011
DOI: 10.18553/jmcp.2011.17.6.456
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pharmacist Intervention and the Proportion of Diabetes Patients Attaining Prevention Objectives in a Multispecialty Medical Group

Abstract: BACKGROUND: Clinical practice recommendations from American Diabetes Association (ADA) include specific prevention goals intended to reduce the risk of diabetic complications. The Healthy People 2010 (HP2010) initiative, updated to Healthy People 2020, proposes similar objectives for improvement of clinical measures and outcomes in patients with diabetes. Clinical pharmacists are gaining an increasing role in providing diabetes management services, including collaborative practice in medical groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 8 publications
0
25
1
Order By: Relevance
“…Patients who were in direct contact with the pharmacist showed better preventive care attributes as required by the management guidelines [12]. The present study has demonstrated that increase in self-monitoring of blood glucose levels may improve glycemic control but this is not in agreement with the results of other studies [13]. It was found that knowledge of HbA1c is poor among diabetic patients.…”
Section: Discussioncontrasting
confidence: 81%
“…Patients who were in direct contact with the pharmacist showed better preventive care attributes as required by the management guidelines [12]. The present study has demonstrated that increase in self-monitoring of blood glucose levels may improve glycemic control but this is not in agreement with the results of other studies [13]. It was found that knowledge of HbA1c is poor among diabetic patients.…”
Section: Discussioncontrasting
confidence: 81%
“…It has been demonstrated in numerous studies that pharmacist management of patients with T2DM in the outpatient setting can improve glycemic levels such as hemoglobin A1c 3 along with blood pressure (BP), cholesterol levels, 4,5 and overall quality of life (QOL). 3,4,6 Since BP and cholesterol levels are significant predictors of long-term macrovascular disease such as coronary artery disease, stroke, and peripheral vascular disease, 7 better control of these clinical markers would presumably decrease CVD risk among diabetic patients.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, understanding the means of cooperation between doctors and pharmacists and ways to avoid barriers to effective collaboration may help with delivery of optimum healthcare services. There is evidence that the addition of a pharmacist to a collaborative, team-based setting can improve performance against quality indicators and national health goals 14 15…”
Section: Introductionmentioning
confidence: 99%